Metamorphic consequences of secular changes in oceanic crust composition and implications for uniformitarianism in the geological record - Palin, R; Dyck, B (Elsevier, 2018)
Cooling of the Earth's mantle since the Meso-Archean is predicted by thermal and petrological models to have induced a secular change in the composition of primary mantle-derived magmas – and thus bulk oceanic crust; in particular, suggesting a decrease in maficity over time. This hypothesis underpins several recent studies that have addressed key geological questions concerning evolving plate tectonic styles, the rates and timing of continental crust formation, comparative planetology, and the emergence of complex life on Earth. Major, minor, and trace element geochemical analyses of (meta)mafic rocks preserved in the geological record allows exploration of this theory, although no consensus currently exists about the magnitude of this change and what compositions – if anything – constitute representative examples of Paleo-, Meso-, or Neo-Archean primitive oceanic crust. In this work, we review the current state of understanding of this issue, and use phase equilibria to examine the different mineral assemblages and rock types that would form during metamorphism of basalt of varying maficity in subduction zone environments. The presence (or absence) of such metamorphic products in the geological record is often used as evidence for (or against) the operation of modern-day subduction-driven plate tectonics on Earth at particular time periods; however, the control that secular changes in composition have on the stability of mineral assemblages diagnostic of subduction-zone metamorphism weakens such uniformitarianistic approaches. Geodynamic interpretations of the Archean metamorphic rock record must therefore employ a different set of petrological criteria for determining tectonothermal histories than those applied to Proterozoic or Phanerozoic equivalents.